2010
DOI: 10.1111/j.1467-9515.2009.00700.x
|View full text |Cite
|
Sign up to set email alerts
|

Older People's Family Contacts and Long‐term Care Expenditure in OECD Countries: A Comparative Approach Using Qualitative Comparative Analysis

Abstract: In recent decades there has been a suggestion that public and private long-term care (LTC) expenditure might be replacing traditional family care for older people. The decline of family contact is known to be more advanced in some OECD countries than others, with southern Europe identified as where family contact is still strong. This article explores at a country level whether there is an association between levels of expenditure on long-term care and the availability of family contacts. Qualitative Comparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In Scandinavia, the move towards occupational welfare and pensions seems less likely to disadvantage women because of their high participation in the labour market. In countries where women are encouraged and incentivized to take traditional caring roles over and above employment and where participation in the labour market is low, occupational welfare systems may pauperize women (Haynes et al . 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In Scandinavia, the move towards occupational welfare and pensions seems less likely to disadvantage women because of their high participation in the labour market. In countries where women are encouraged and incentivized to take traditional caring roles over and above employment and where participation in the labour market is low, occupational welfare systems may pauperize women (Haynes et al . 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Children (aged 0-14) are assumed to live with their parents who are represented in the working-age population. The elderly (aged 65+) are also highly dependent on the working-age population for care and support (Haynes et al, 2010). Despite empirical evidence which suggests that a proportion of previously urban retirees choose to move to the countryside (Brown, Kulcsár, Kulcsár, & Obádovics, 2005;Kok, 1999), residential mobility of the European elderly is generally low (Angelini & Laferrère, 2012).…”
Section: Population Dependency For Children (Aged 0-14) and The Eldermentioning
confidence: 99%
“…Children are most likely to live with their parents and hence do not have a direct influence on where they live, although school location may affect adult decision-making. The elderly may live alone, but typically are highly dependent on the working-age population who are the main providers of care and support (Haynes, Hill, & Banks, 2010). Capturing these types of preferences and dependencies in an agespecific way would make population distribution models more representative of real-world patterns and thus more applicable in the development of future demographic scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Netherlands, "the first country to introduce a universal and mandatory insurance program for LTC", the expenditure on LTC in 2007 was €17.6 billion (Van Den Berg & Schut, 2010) (approximately US$ 24.27 billion as of November 2011) with 65% of the total expenditure allocated to the support of the elderly and chronically ill. On the other hand in Hong Kong, where no formal LTC system exists, the nation as a whole was estimated to have spent around 1.4% of its GDP on long-term related care in 2004 (Chung, et al, 2009). A report into the expenditure on LTC in 2000 within OECD countries found that although there were large variations in spending as a percentage of GDP, public and private sector combined spending accounted for an average of 1.21% of GDP across the OECD with an interquartile range of 0.70% (Haynes, Hill, & Banks, 2010). By 2009 the average spend in the OECD had risen to 1.3% of GDP (OECD, 2011) although we should point out that a number of reforms took place in this period in which LTC has shifted its focus towards meeting the needs of those with the highest levels of care needs.…”
Section: Expenditure On Long-term Carementioning
confidence: 99%